Efficient biosynthesis of heterodimeric C3-aryl pyrroloindoline alkaloids. Issue 1 (December 2018) - Tian, Wenya; Sun, Chenghai; Zheng, Mei; Harmer, Jeffrey; Yu, Mingjia; Zhang, Yanan; Peng, Haidong; Zhu, Dongqing; Deng, Zixin; Chen, Shi-Lu; Mobli, Mehdi; Jia, Xinying; et al.
Abstract Many natural products contain the hexahydropyrrolo[2, 3-b ]indole (HPI) framework. HPI containing chemicals exhibit various biological activities and distinguishable structural arrangement. This structural complexity renders chemical synthesis very challenging. Here, through investigating the biosynthesis of a naturally occurring C3 -aryl HPI, naseseazine C (NAS-C), we identify a P450 enzyme (NascB) and reveal that NascB catalyzes a radical cascade reaction to form intramolecular and intermolecular carbon–carbon bonds with both regio- and stereo-specificity. Surprisingly, the limited freedom is allowed in specificity to generate four types of C3 -aryl HPI scaffolds, and two of them were not previously observed. By incorporating NascB into an engineered strain ofE. coli, we develop a whole-cell biocatalysis system for efficient production of NAS-C and 30 NAS analogs. Interestingly, we find that some of these analogs exhibit potent neuroprotective properties. Thus, our biocatalytic methodology offers an efficient and simple route to generate difficult HPI framework containing chemicals. The hexahydropyrrolo[2, 3-b ]indole (HPI) framework is found in many natural products. Here, the authors discover a P450 enzyme and develop a whole-cell biocatalysis system that produces the HPI naseseazine C (NAS-C) and 30 NAS-C analogs, several of which show neuroprotective properties.